My HAIR SALON: Collaboration of Right Brain and Left Brain Students in the Mind Mapping Model for Statistical Material - Darmayanti, Rani; Arif, Viky Risnanda; Usmiyatun, Usmiyatun (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
People who are good at math are the same as people who are mainly left-brained, or conversely, people who like art like drawing, music, dancing, etc., are the same as right-brained people. This is why the analysis tool "HAIR SALON" was born, used in the Mind Map model related to the brain's two hemispheres, the left brain and the right brain. "HAIR SALON" media is used to make the learning process interesting. Mind maps are the most effective and efficient way to collect, store, and generate data from students' brains to describe how learning outcomes are affected and the effects of brain usage. Right and left brain dominant. This study aims to improve students' learning outcomes in Mathematics by using the mind map model to improve learning outcomes. Middle school students study statistical materials. The method that will be used in this study is the descriptive method. This form of research is classroom action research (PTK). How to collect data, analyze techniques, and describe the interpretations and conclusions of the classroom audience will be discussed